2020
DOI: 10.3390/ijms21041207
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Glycosylated Platycoside E to Deapiose-Xylosylated Platycodin D by Cytolase PCL5

Abstract: Platycosides, the saponins abundant in Platycodi radix (the root of Platycodon grandiflorum), have diverse pharmacological activities and have been used as food supplements. Since deglycosylated saponins exhibit higher biological activity than glycosylated saponins, efforts are on to enzymatically convert glycosylated platycosides to deglycosylated platycosides; however, the lack of diversity and specificities of these enzymes has limited the kinds of platycosides that can be deglycosylated. In the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 42 publications
3
15
0
Order By: Relevance
“…It has been found that platycoside E is a precursor of platycodin D, and PE can be converted to PD by enzyme catalysis. Their biological activities can be increased and their bioavailability and cell permeability would be improved due to their reduced size resulted by de-glycosylation of saponins 17 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that platycoside E is a precursor of platycodin D, and PE can be converted to PD by enzyme catalysis. Their biological activities can be increased and their bioavailability and cell permeability would be improved due to their reduced size resulted by de-glycosylation of saponins 17 .…”
Section: Introductionmentioning
confidence: 99%
“…(Jeong et al, 2014) converted platycoside E into platycodin D, which indicates that these enzymes hydrolyze only the glucose moiety at the C-3 position of the platycosides. In contrast, crude enzyme and cytolase from A. niger (Shin et al, 2020), and pectinase from Aspergillus aculeatus (Ju et al, 2020) converted platycoside E into deapiose-dexylosylated platycodin D and glucosylated platyconic acid, respectively, hydrolyzing glycosides at the C-28 position. However, the enzyme that converts into deglucosylated platycodin D is only the recombinant β-glucosidase from D. turgidum (Kang et al, 2019).…”
Section: Hydrolytic Pathway Of Platycoside E To Deglucosyl Platycodin D By Pluszyme 2000pmentioning
confidence: 93%
“…Therefore, various methods such as heating (Kim et al, 2000), acid treatment (Bae et al, 2004), and biotransformation (Kim et al, 2019a;Shin et al, 2018) have been used to deglycosylate saponins. Among these, the enzymatic biotransformation of platycosides shows the highest selectivity and productivity, which has been demonstrated in diverse studies using a crude enzyme from Aspergillus niger (Wie et al, 2007), β-galactosidase from Aspergillus oryzae (Ha et al, 2010), β-glucosidase from Aspergillus usamii (Ahn et al, 2018), recombinant β-glucosidases from Caldicellulosiruptor bescii (Kil et al, 2019), Caldicellulosiruptor owensensis (Shin et al, 2019), and Dictyoglomus turgidum (Kang et al, 2019), and commercial enzymes, such as cellulase (Ha et al, 2010), laminarinase (Jeong et al, 2014), snailase (Li et al, 2012), pectinase (Ju et al, 2020), and cytolase (Shin et al, 2020). β-Glucosidase from D. turgidum was the only enzyme that produced deglucosylated platycodin D and showed the highest lipoxygenase inhibitory activity among all platycosides.…”
Section: Introductionmentioning
confidence: 99%
“…Platycoside E, platycodin D3, platycodin D, and deapiosylated platycodin D were purchased from Ambo Laboratories (Daejeon, Republic of Korea). Deapiose-xylosylated platycodin D was prepared as previously reported [23] and used as a standard. All other reagents were purchased from Sigma-Aldrich (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Caldicellulosiruptor bescii [18], Caldicellulosiruptor owensensis [19], Dictyoglomus turgidum [20], and cellulase [21], pectinase [22], and cytolase PCL5 [23]. Among these, cytolase PCL5 is the only enzyme that can hydrolyze the outer glucose at C-3 and xylose and apiose at C-28 in platycoside E, the most abundant saponin in balloon flower (Figure 1).…”
Section: Introductionmentioning
confidence: 99%